Effect of vitamin B6 on brain damage in valproic acid induced toxicity - Turkyilmaz, Ismet Burcu; Altas, Nilay; Arisan, Inci; Yanardag, Refiye (WILEY, 2021)
Valproic acid (VPA) is an efficient antiepileptic drug widely used for the treatment of epilepsy and other seizures in both children and adults. It is also reported to have side and toxic effects on many organs and tissues. Vitamin B-6 (Vit B-6) is a well-described water-soluble vitamin, which has an antioxidant effect. In this study, we aimed to investigate the protective effect of Vit B-6 on VPA-induced brain injury. Male Sprague-Dawley rats were divided into four groups. Group I, control animals; Group II, Vit B-6 (50 mg/kg/day) given rats; Group III, VPA (500 mg/kg/day) given rats; Group IV, VPA and Vit B-6 given rats at same dose and time. VPA and Vit B-6 were administered intraperitoneally and orally, respectively, for 7 days. At the end of the experiments, the rats were sacrificed and brain tissues were taken. Protein carbonyl and sialic acid levels, xanthine oxidase, adenosine deaminase, acetylcholine esterase, lactate dehydrogenase, myeloperoxidase activities, total oxidant status, and reactive oxygen species levels were found to be increased, while glutathione and total antioxidant capacity levels, catalase, superoxide dismutase, glutathione-S-transferase, paraoxonase, and glutathione reductase activities were found to be decreased in the VPA group. Administration of Vit B-6 reversed these defects in the VPA group. These findings indicate that Vit B-6 has a protective effect on VPA-induced brain damage.
Keywords: brain; oxidative stress; toxicity; valproic acid; vitamin B6; ANTIOXIDANT SYSTEM; POLYSIALIC ACID; IN-VIVO; RATS; ACETYLCHOLINESTERASE; GLUTATHIONE; INJURY; LIVER; SERUM; Biochemistry & Molecular Biology; Toxicology